Homesickness in developing world expatriates and coping strategies. (August 2021) - Hack-Polay, Dieu; Mahmoud, Ali B
This article examines the developing world expatriates' experience of homesickness when they are deployed to western countries. The research considers the consequences of being homesick on the expatriates and their organisations; the paper then clarifies the strategies used by the expatriates to cope with the condition. The research employed qualitative research built on unstructured interviews with expatriates from the developing world who have been deployed in western countries by their employing multinational. The findings revealed that homesickness has consequences for both expatriates and organisations. These consequences include psycho-social disorder, deterioration of physical health which damagingly affect individual wellbeing, work outcomes and organisational commitment. The practical implications centre on the opportunity for policy and strategy formulation by international HRM within organisations to improve the mental health of developing world expatriates, thus seeding the ingredients for better performance and job satisfaction. Our study makes significant additions to the expatriate literature in exposing the homesickness experiences of expatriates from the developing world in advanced economies. We identify two main coping strategies used by expatriates. The research explicates how developing world expatriates use these strategies in practices.